THE AM CVN SYSTEMS – THE FINAL STAGE OF BINARY WHITE DWARF EVOLUTION - Solheim, J. -E.; Nasser, M. R. (Одеські астрономічні публікації, 2017)
The last decade has shown a surge in research on the Interacting Binary White Dwarf s (IB-WDs), or Helium CVs, also called AM CVn systems. We have witnessed long photometric campaigns, time resolved spectroscopy, UV and X-ray observations, and modelling of disc structure, disc atmosphere and their evolution. Recently several new members of the AM CVn family have been added, and a new subclass - double degenerate polars has been identified. A review of the research on AM CVn systems during the last decade is given, and some problems to be solved in the future are presented.